Upaya Peningkatan Pemahaman dan Pentingnya Wawasan Nusantara Bagi Mahasiswa Ilmu Sosial - Silfhani Elisabet Manurung; Abednego Purba; Alfrendo Nainggolan; Frisca Devina D. Simanjuntak; Putri Rahmadani; Selviyana Sari; Sri Yunita (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2022)
This study seeks to find out how efforts can be made to increase social studies students' understanding and insight about the importance of the archipelago. Students must play a role in supporting the insight of the archipelago and preserving the richness of Indonesian culture in order to realize the ideals of the Indonesian nation. Research is carried out by seeking sources and going directly to the location for a question and answer session through mutual commitment and agreement. The method used in this research is descriptive method and qualitative case. This is where we interviewed directly by asking a number of questions about our group's material. An understanding of the prospects for Indonesian students is of course very important for the life of the nation and state and for the realization of the ideals of the Indonesian nation.